Polymorphism in the 5′-Flanking Region of Human Glutamate-Cysteine Ligase Modifier Subunit Gene Is Associated With Myocardial Infarction - Nakamura, Shin-ichi; Kugiyama, Kiyotaka; Sugiyama, Seigo; Miyamoto, Shinji; Koide, Shun-ichi; Fukushima, Hironobu; Honda, Osamu; Yoshimura, Michihiro; Ogawa, Hisao (Circulation (New York, N.Y.), 2002)
Background — Human glutamate-cysteine ligase (GCL) is a rate-limiting enzyme for the synthesis of glutathione that plays a crucial role in antioxidant defense mechanisms in most mammalian cells, including vascular cells. Oxidants transcriptionally upregulate GCL genes for glutathione synthesis, providing a protective mechanism against oxidative stress-induced cellular dysfunction. This study examined the hypothesis that variation in the GCL genes may be associated with coronary artery disease in which oxidative stress plays a pathogenetic role. Methods and Results — We searched for the common variants in the 5′-flanking region of the GCL modifier subunit (GCLM) gene in patients with myocardial infarction (MI). We found a polymorphism (−588C/T) in which the T allele showed lower promoter activity (40% to 50% of C allele) in response to oxidants in the luciferase reporter gene assay. Allele frequencies were determined by polymerase chain reaction-based analysis of restriction fragment length polymorphism in 429 patients with MI and 428 control subjects (as defined by angiography) in Kumamoto Prefecture, Japan. The frequency of the T polymorphism was significantly higher in the MI group than in the control group (CT and TT genotypes: 31.5% in MI group versus 19.2% in control group; P <0.001). In multiple logistic regression analysis, the T polymorphism was a risk factor for MI independent of traditional coronary artery disease risk factors (odds ratio, 1.98; 95% confidence interval, 1.38 to 2.83; P <0.001). Conclusions — These findings suggest that the −588T polymorphism of the GCLM gene may suppress GCLM gene induction in response to oxidants and that it is a genetic risk factor for MI.